2022
DOI: 10.1039/d2dt01827f
|View full text |Cite
|
Sign up to set email alerts
|

Unique CoWO4@WO3heterostructured nanosheets with superior electrochemical performances for all-solid-state supercapacitors

Abstract: High performance asymmetric supercapacitors assembled with heterostructured core-shell CoWO4@WO3-1 cathodes and Ov-NiMoO4 anodes, showing a maximum area energy density of 13.93 mW h cm−2 and keeping 98.1% capacity retention over 20 000 cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…4e shows that the W 4f spectra can split into two peaks siting at 35.66 and 37.79 eV from W 4f 7/2 and W 4f 5/2 , respectively, which proved that W has been successfully doped into MnO x /MnWO 4 @C composites. 24 The C 1s spectrum in Fig. S3 † can split into three peaks, with the major peak of 284.89 eV representing the sp 2 hybridized carbon (CC bonds).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4e shows that the W 4f spectra can split into two peaks siting at 35.66 and 37.79 eV from W 4f 7/2 and W 4f 5/2 , respectively, which proved that W has been successfully doped into MnO x /MnWO 4 @C composites. 24 The C 1s spectrum in Fig. S3 † can split into three peaks, with the major peak of 284.89 eV representing the sp 2 hybridized carbon (CC bonds).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the areal energy density (E S , mW h cm −2 ) and areal power density ( P S , mW cm −2 ) of flexible supercapacitors were calculated using formulas (2) and (3) as follows:where I (mA), Δ t (s), Δ V (V) and S (cm 2 ) represent the discharge current, discharge time by GCD curves, voltage window of the device, and the total area of the double electrodes of the device, respectively. 23,24…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Ma et al reported an areal-specific capacity of 578.6 mF cm −2 at 0.5 mA cm −2 for CoWO 4 @WO 3−1 with 53.9% retention in the rate capacity. 25 Pan et al , reported Ti 3 C 2 T x /WO x supported on flexible carbon cloth to deliver 164 F g −1 at 5 mA cm −2 . 26 The TiO 2 /WO 3 heterojunction with engineered O vac for a lowered work function and accelerated charge transmission at an electrochemical interface has also been reported (102 F g −1 at 1 A g −1 ; 97% retention).…”
Section: Introductionmentioning
confidence: 99%